Syria and the Palestinians : the clash of nationalisms - Talhami, Ghada Hashem (University Press of Florida, 2001)
''A critically important addition to our knowledge of Syria and the Palestinians.''-- William W. Haddad, California State University, Fullerton''A powerful and persuasive contribution to the discourse on Arab nationalism. It is based on original research never before seen in the English language.